Theoretical study of metal-metal cooperativity in the homogeneous water gas shift reaction - Kuriakose, Nishamol; Kadam, Shantanu; Vanka, Kumar (Inorganic Chemistry, 2012)
The possibility of metal-metal cooperativity in improving the yield of the homogeneous water gas shift reaction (WGSR) has been investigated through full quantum mechanical density functional theory calculations. The calculations indicate that bimetallic catalysts would be likely to be more highly active than mononuclear metal-based catalysts for the WGSR. The results have implications for the design of improved WGSR catalysts in the future.